Kajian Terhadap Landasan Filosofi Pantun Minangkabau - Erizal Gani (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2009)
The purpose of this research is to reveal (1) the nature of Minangkabau quatrains, (2) fundamental philosophy of Minangkabau quatrains and (3) the functions of Minangkabau quatrains. This research is uses the descriptive qualitative design. The results of the research show that (1) Minangkabau quatrains use Minangkabau language as means of communication, follow the philosophy of “from, by and for” Minangkabau society which are inspired from things related to Minangkabau and its thinking pattern and come from Minangkabau society, (2) the fundamental philosophy of Minangkabau quatrains is “alam takambang jadi guru”, (3) Minangkabau quatrains have some multifunctions for the life of the Minangkabau society. Keywords: minangkabau’s magic spells, fundamental philosophy, and function.